Between the Profiles Pay Per View and the Protection of Personal Data: the Product is You - Chávez Valdivia, Ana Karin (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2017)
Perhaps in the past was difficult to imagine that the moment in which someone could register each purchase that has been made, each book that has been read or each thing that has been said would come. That there would be companies storing data about our physical activity, behaviors, preferences and choices all the time. Most of the personal data comes from acts as daily as installing an application, completing a form, purchasing a product or requesting a service. This information provided sometimes consciously, voluntarily and with relative knowledge of the destination that will have, contrasts with situations in which data are inferred, deduced, extracted and manipulated. In this sense, within a context in which the only access to the database has been left behind to give way to the creation of these by third parties, we wonder about the possible denaturation of the personal data and sensitive information that when get transformed in raw material through the analysis of existent connections and extraction of new data implicit in the multitude of information compiled in public or private databases, would convert people into an essential product for the market; while the development of citizen profiles pay per view would allow predicting behaviors, selections and multiple deployments in different aspects of our lives. It is probable that in the defenselessness condition where we are now for having passed from personal space to social one and from there to the market many times without our knowledge and consent makes necessary to reconsider the current forms of protection and mechanisms of legal protection around our personal data.